2023
DOI: 10.3390/ijms241210189
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Relevance of NaV1.8-Induced Atrial Arrhythmogenic Triggers in a Human SCN10A Knock-Out Stem Cell Model

Abstract: In heart failure and atrial fibrillation, a persistent Na+ current (INaL) exerts detrimental effects on cellular electrophysiology and can induce arrhythmias. We have recently shown that NaV1.8 contributes to arrhythmogenesis by inducing a INaL. Genome-wide association studies indicate that mutations in the SCN10A gene (NaV1.8) are associated with increased risk for arrhythmias, Brugada syndrome, and sudden cardiac death. However, the mediation of these NaV1.8-related effects, whether through cardiac ganglia o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…iPSC-CM were incubated with either Iso (50 nmol/L, or Iso + PF-01247324 (1 µmol/L, Sigma-Aldrich, Taufkirchen, Germany) for 15 min before starting measurements. Regarding the specificity of Na V 1.8 blockers, there are already published data that have demonstrated the specificity of PF-01247324 and showed that it is an efficacious inhibitor of Na V 1.8 [ 21 , 22 , 73 , 74 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…iPSC-CM were incubated with either Iso (50 nmol/L, or Iso + PF-01247324 (1 µmol/L, Sigma-Aldrich, Taufkirchen, Germany) for 15 min before starting measurements. Regarding the specificity of Na V 1.8 blockers, there are already published data that have demonstrated the specificity of PF-01247324 and showed that it is an efficacious inhibitor of Na V 1.8 [ 21 , 22 , 73 , 74 ].…”
Section: Methodsmentioning
confidence: 99%
“…Patch-clamp experiments were performed as previously described [ 21 , 22 , 74 , 75 ]. For action potential recordings, we employed the whole-cell patch-clamp technique in the current clamp configuration.…”
Section: Methodsmentioning
confidence: 99%
“…One such study, published as part of the present Special Issue, performed by Hartman et al aimed to investigate the electrophysiological contribution of Na V 1.8 (a voltage-gated sodium channel) to the generation of atrial arrhythmogenesis by using a human SCN10A knock-out stem cell model. The results of the study conclusively showed that Na V 1.8 inhibition can modulate pro-arrhythmogenic triggers in atrial cardiomyocytes, suggesting its potential usefulness as a target in arrhythmogenic strategies [ 19 ]. The results of this particular study thus confirm the results of other studies in this research field, which may soon have significant therapeutic implications [ 20 ].…”
Section: Editorialmentioning
confidence: 99%
“…This impacts Na V 1.5 function, cardiac conduction velocities, and arrhythmia susceptibility. A recent study has shown that the SCN10A gene (Na V 1.8) contributes to I NaL formation in human atrial cardiomyocytes, and CRISPR/Cas9 deletion of this gene modulates proarrhythmogenic triggers in human atrial cardiomyocytes [167].…”
Section: Scn1b and Scn10amentioning
confidence: 99%